2001
DOI: 10.1523/jneurosci.21-15-05660.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulins Increase α7 Nicotinic Acetylcholine Receptors and Enhance Excitatory Synaptic Transmission in GABAergic Interneurons of the Hippocampus

Abstract: Neuregulins are highly expressed in the CNS, especially in cholinergic neurons. We have examined the effect of neuregulin on nicotinic acetylcholine receptors (nAChRs) in neurons dissociated from the rat hippocampus. Rapid application of acetylcholine (ACh) induced a rapidly rising and decaying inward current in some of the neurons, which was completely blocked by methyllycaconitine, a specific antagonist of the ␣7 subunit of the nAChR. When the cells were treated with 5 nM neuregulin (NRG1-␤1) for 2-4 d, a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 51 publications
6
111
0
Order By: Relevance
“…Interestingly, in vivo, CRD-NRG is expressed in the appropriate SG preganglionic inputs prior to synaptogenesis and is detected in presynaptic terminals (Yang et al, 1998). Neuregulin also increases ␣7-mediated ACh responses in dissociated rat hippocampal neurons (Liu et al, 2001). These studies support the potential role of neuregulins as relevant input-derived regulatory signals that increase neuronal nAChR expression levels.…”
Section: Regulatory Signals That Mediate the Effects Of Synaptic Partmentioning
confidence: 60%
“…Interestingly, in vivo, CRD-NRG is expressed in the appropriate SG preganglionic inputs prior to synaptogenesis and is detected in presynaptic terminals (Yang et al, 1998). Neuregulin also increases ␣7-mediated ACh responses in dissociated rat hippocampal neurons (Liu et al, 2001). These studies support the potential role of neuregulins as relevant input-derived regulatory signals that increase neuronal nAChR expression levels.…”
Section: Regulatory Signals That Mediate the Effects Of Synaptic Partmentioning
confidence: 60%
“…31 In the central nervous system, NRG-1 promotes the switch from the immature form of NMDAR, which contains primarily NR2B subunits to one containing more NR2C subunits. 17 NRG-1 also potentiates a7 nicotinic acetylcholine receptor transmission in hippocampal neurons, 20 and expression of the b2 subunit of the gamino butyric acid receptor in cerebellar granule cells. 19 Thus, the relative increase in type I expression in schizophrenia brain might alter neuronal signaling of NRG-1 per se, or it may be an indirect factor in putative abnormalities of NMDA, nicotinic, and/or GABA receptor-related signaling in schizophrenia brain.…”
Section: Discussionmentioning
confidence: 92%
“…These NRG-1 isoforms play multiple and distinct functions in neuronal development, and abnormalities in brain development have been implicated in schizophrenia. Moreover, NRG-1 regulates the expression and plasticity of N-methyl-daspartate receptors (NMDAR), of the b2 subunit of the g-amino butyric acid receptor, and of nicotinic acetylcholine receptor subtypes including a5, a7, and b4 subunits [17][18][19][20] , some of which also may be involved in genetic risk for schizophrenia. 21,22 Thus, while genetic evidence implicates NRG-1 as a schizophrenia susceptibility gene, and the biology of NRG-1 overlaps with diverse aspects of the putative biology of schizophrenia, there have been no published studies of NRG-1 expression in the schizophrenic brain tissue, and little is known about whether a specific NRG-1 isoform contributes to the risk for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Two families of neuregulin 1 isoforms were identified originally by virtue of their ability to regulate the expression of nAChRs at peripheral synapses (Falls et al, 1993;Yang et al, 1998). Subsequently, a number of investigators have demonstrated that neuregulin also can increase the synaptic expression of α7-containing nAChRs at central synapses (Kawai et al, 2002;Liu et al, 2001), and our laboratories have extended this story by demonstrating that neuregulin 1 signaling also regulates presynaptic expression and targeting of the α7 nAChRs (Role and Talmage, unpublished). These latter studies are particularly intriguing in light of the well-documented deficits in α7 nAChRs in schizophrenics, the association of this deficit with defects in P50 measures of auditory gating in schizophrenics and their first degree relatives, and the association of α7 subunit gene promoter polymorphisms with these deficits (see chapter by Martin and Freedman, this volume; Leonard et al, 1996Leonard et al, , 2002.…”
Section: B Potential Role Of Neuregulinmentioning
confidence: 99%